A Novel Approach to Debriefing Medical Simulations: The Six Thinking Hats - Zhang, Xiao Chi (Cureus, 2018)
Simulation has become a standard training method in emergency medicine (EM). Specifically, post-simulation debriefings offer participants the opportunity for reflection while exposing their knowledge and practice gaps. The educational yield of these debriefings, however, is contingent on the debriefer's skills. Without professional development, faculty and educators may not be equipped with supportive debriefing strategies. We propose the Six Thinking Hats (6TH), originally developed by Edward de Bono (1970) as a debriefing framework to support effective, high-yield debriefing conversations. The six colored hats represent six unique approaches to critical thinking. The white hat represents the facts; the green hat, creativity and next steps; the yellow hat, benefits/optimism; the red hat, emotions; the black hat, judgments; and the blue hat, facilitation. Four junior faculty members underwent a one-hour didactic and one-hour immersive workshop on the 6TH. Two simulation cases were randomly selected from archived simulation cases, which were used for the debriefing process. Each team consisted of one EM resident and one EM faculty. After each simulated case, the facilitator introduced the 6TH at the start of the debriefing, explaining the rules of engagement and the general sequence of hats to be used. Physical hats were worn by the facilitator at the beginning of the session and changed throughout stages of the debriefing, to remind participants of the type of thinking that was taking place at any given time. Participants who were provided with a colored hat prompt that physically described the type of thinking being employed throughout stages of the debriefing were better able to stay within that respective thinking frame during the discussion, compared to participants who were not provided this visual prompt. Participants of both simulation sessions agreed that the 6TH debriefing style was successful in creating a non-judgmental, comfortable environment that supported open discussion. The 6TH has the potential to be adopted as a debriefing framework, particularly for junior faculty members without extensive debriefing training. The 6TH is intuitive and has been marked by success in the organizational psychology literature. Faculty development on the 6TH will be essential if this framework is to be used as a debriefing model for educators in health care.